Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1159/000337351
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Clinical Management and Diagnosis following DaTscan™ SPECT Imaging in Patients with Clinically Uncertain Parkinsonian Syndromes: A 12-Week Follow-Up Study

Abstract: Background: An accurate diagnosis is important for timely and adequate treatment in patients with clinically uncertain parkinsonian syndrome (CUPS). Objective: The objective of this study was to assess safety and changes in clinical management, diagnosis and quality of life (QoL) at 4 and 12 weeks following DaTscan™ (ioflupane [123I] injection) imaging in patients with CUPS. Methods: This randomized, open-label, single-dose, multicenter trial was carried out in patients with CUPS who were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
5
15
0
Order By: Relevance
“…Following an interim analysis of our data, we previously reported that significantly more patients in the DaTscan group had a change in their clinical management at approximately 12 weeks post-treatment compared with patients in the control group 25. Similar results were obtained at 1-year follow-up, with significantly more patients in the DaTscan group (41%) having a change in clinical management compared with the control group (22%).…”
Section: Discussionsupporting
confidence: 77%
“…Following an interim analysis of our data, we previously reported that significantly more patients in the DaTscan group had a change in their clinical management at approximately 12 weeks post-treatment compared with patients in the control group 25. Similar results were obtained at 1-year follow-up, with significantly more patients in the DaTscan group (41%) having a change in clinical management compared with the control group (22%).…”
Section: Discussionsupporting
confidence: 77%
“…31 A presynaptic single photon emission computed tomography (SPECT) agent for dopamine transporter has been recently approved for clinical use to distinguish Parkinson's disease from essential tremor based on preserved uptake of the tracer in the latter. 32 Similar results with corresponding dopamine transporter PET ligands are expected.…”
Section: Movement Disorders and Pet Imagingsupporting
confidence: 75%
“…Other studies have shown a change in clinical management after imaging in 50% [8], 63% [2], and 72% [9] of all cases. Here, we expand upon these prior studies by assessing quantitative estimates of diagnostic certainty before and after imaging and by assessing the degree to which the asymmetry in the results corresponds to asymmetric symptoms in the clinical examination.…”
Section: Introductionmentioning
confidence: 99%